Health and Safety of Limited English Speaking Asian Homecare Aides in Chicago: A Pilot Study. Issue 1 (January 2019) - Zhang, Jing; Buchanan, Susan N.; Rospenda, Kathleen M.; Zanoni, Joseph
Abstract : Objectives: To identify health and safety hazards and needs among limited English speaking Asian home care aides, and characterize their acculturation status and how it affects their health and safety. Methods: Surveyed 60 home care aides and interviewed six home care service providers to assess health and safety hazards and needs of the study population. Results: The majority of the study participants were older and did not speak English or did not speak English well. They communicated with senior clients in their native language only or most of the time. Many experienced work related injuries and musculoskeletal pain. Discussion: The Asian homecare aides met the critical needs of an aging community. They experienced many challenges working as a home care aide and as a result of cultural barriers.